MANDAU: A TRADITIONAL WEAPON RICH IN SYMBOLISM AND SPIRITUAL MEANING - Kaharap, Mongga; Misrita, Misrita; Zulkarnain, Zulkarnain (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2024)
This study explored the cultural, symbolic, and spiritual significance of the Mandau, a traditional weapon deeply rooted in the heritage of the Dayak people in Kalimantan. More than a tool for hunting and self-defense, the Mandau represented profound values such as bravery, communal unity, and respect for ancestors. By employing qualitative descriptive methods combined with semantic analysis, the research investigated the intricate symbolic meanings behind each part of the Mandau. Data collection involved interviews with skilled Mandau craftsmen and respected cultural leaders, along with a thorough review of existing literature on the subject. The findings revealed that the Mandau held a central role in Dayak culture, symbolizing identity, protection, and spiritual connection. Additionally, the research demonstrated the Mandau's potential as a teaching medium in English language education, particularly in fostering contextual understanding and promoting cross-cultural awareness. This study underscored the value of incorporating local cultural elements into global educational frameworks, highlighting how culturally meaningful artifacts could serve as powerful tools for language learning and cultural exchange.